Studien zu Ritual und sozialgeschichte im Alten Orient = Studies on ritual and society in the ancient Near East : Tartuer Symposien, 1998-2004 - Kämmerer, Thomas R. (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2007)
This volume contains the revised versions of lectures that were delivered by scholars from Germany, England, USA, Finland and, more recently, Russia to the first five international symposia on ancient oriental languages and cultures held between 1998 and 2004 at the Faculty of Theology of the University of Tartu, Estonia. Particular emphasis is placed on the analysis of specific problems of the history of religion and medicine, of linguistics and of the archaeology of the Eastern Mediterranean.